2022
DOI: 10.1177/00113921221097157
|View full text |Cite
|
Sign up to set email alerts
|

Spectacularising narratives on femicide in South Africa: A decolonial feminist analysis

Abstract: How are we to think about femicide in South Africa – a country with one of the highest rates of gendered violence, globally? The rate of women murdered in South Africa is around five times the global average and at least half of women who are murdered die at the hands of an intimate partner. Every so often, a South African woman’s murder is propelled into national (and sometimes international) media discourse. How these crimes are reported are important for shaping public consciousness about crimes against wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Thus, preventing GBV in the African context and elsewhere in the world upholds and respects these inherent human rights. Furthermore, this infringement of fundamental human rights disrupts societal harmony and social cohesion (Boonzaier 2023). This means that communities free from violence are more peaceful, stable, and conducive to growth and development.…”
Section: Self-defencementioning
confidence: 99%
“…Thus, preventing GBV in the African context and elsewhere in the world upholds and respects these inherent human rights. Furthermore, this infringement of fundamental human rights disrupts societal harmony and social cohesion (Boonzaier 2023). This means that communities free from violence are more peaceful, stable, and conducive to growth and development.…”
Section: Self-defencementioning
confidence: 99%
“…And with stagnated gender reform at this level, it is not surprising that there continues to be a lack of opportunity and support for women in coaching (Norman, 2008 ). However, research suggests that such dynamics are even more complicated in the African region, where women face additional patriarchal, hegemonic and misogynistic challenges to autonomy, such as femicide, child marriages, female genital mutilation and inheritance rights issues (Demirgüç-Kunt et al, 2013 ; Petroni et al, 2017 ; Obiora et al, 2020 ; Boonzaier, 2022 ).…”
Section: Representation Of Women In Sport Coachingmentioning
confidence: 99%
“…The study found that the violation of women's human rights often leads to a regrettable number of fatalities that victims succumb to daily. Literature searches show that nothing has been done to critically examine the right to life for women in light of the horrendous femicide atrocities committed in South Africa without regard for women's human rights (Yalch & Levendosky, 2018, Ramsoomar, Gibbs, Machisa, 2019& Boonzaier, 2022. Furthermore, a study conducted by Mathebula (2021) postulates that campaigns against lethal and brutal violence perpetrated against women have been increasingly gaining traction over the past five decades.…”
Section: Femicidementioning
confidence: 99%
“…Globally, alcohol use is an important public health concern which often contributes to Intimate Partner Violence (IPV/F) and Femicide and Gender Based Violence (GBV). Researchers and activists have indicated the contribution of harmful substance and alcohol use conditions to the severity and circumstances of intimate partner violence (Du Plessis, 2019;Brodie, 2020& Boonzaier, 2022. There has been much debate over alcohol use and intimate partner violence on whether it is truly causal.…”
Section: Introductionmentioning
confidence: 99%